2017
DOI: 10.3390/su9101913
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Linkage Network Dynamic Structures of Chinese Maritime Ports through Automatic Information System Data

Abstract: Abstract:Marine economic cooperation has emerged as a major theme in this era of globalization; hence, maritime network connectivity and dynamics have attracted more and more attention. Port construction and maritime route improvements increase maritime trade and thus facilitate economic viability and resource sustainability. This paper reveals the regional dimension of inter-port linkage dynamic structure of Chinese maritime ports from a complex multilayer perspective that is meaningful for strategic forecast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Network properties were actively researched at the global scale in the case of container shipping (Deng et al, 2009;Hu and Zhu, 2009) as well as solid bulkers and oil tankers (Kaluza et al, 2010;Cui, 2014), most of the time concluding to the existence of power-law characteristics in the distribution of degree centrality, a necessary condition for the network to be scale-free. The analysis of global maritime networks using such methods revealed important hidden information, such as the hierarchy of port centrality (Zhao et al, 2014), at different connectivity levels (Yu et al, 2017) and based on links rather than nodes (Zhang et al, 2018).…”
Section: From Graph Theory To Complex Networkmentioning
confidence: 99%
“…Network properties were actively researched at the global scale in the case of container shipping (Deng et al, 2009;Hu and Zhu, 2009) as well as solid bulkers and oil tankers (Kaluza et al, 2010;Cui, 2014), most of the time concluding to the existence of power-law characteristics in the distribution of degree centrality, a necessary condition for the network to be scale-free. The analysis of global maritime networks using such methods revealed important hidden information, such as the hierarchy of port centrality (Zhao et al, 2014), at different connectivity levels (Yu et al, 2017) and based on links rather than nodes (Zhang et al, 2018).…”
Section: From Graph Theory To Complex Networkmentioning
confidence: 99%
“…Research on maritime network structure mostly focuses on topology using indicators derived from graph theory, such as node degree, shortest path lengths, clustering coefficient, and others, see Table 1. Other indicators can also be used to study network structure, including linkage intensity, linkage tightness, spatial isolation, and linkage concentration [11]. Maritime network topology structure evolution can be further studied through the changes of indicators over time [12,13,14,15,16,17].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In related research of maritime transportation, scholars mainly use data mining methods to reveal the characteristics of the maritime network structure [32], the maritime network evolution mechanism [33], the change law and the evolution mode of the traffic flow in the sea [34] through constructing maritime network, so as to master the changes of the pattern of maritime trade. Mou et al [35] have revealed the relevance and cargo flow mode of regional maritime trade patterns along the MSR through different types of maritime networks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The dynamic changes of three types of cargo ships can effectively reflect the characteristics of the changes of maritime trade among ports, countries and regions. Therefore, this paper chooses the trajectory of oil tankers to explore the relationship between shipping and oil price.In related research of maritime transportation, scholars mainly use data mining methods to reveal the characteristics of the maritime network structure [32], the maritime network evolution mechanism [33], the change law and the evolution mode of the traffic flow in the sea [34] through constructing maritime network, so as to master the changes of the pattern of maritime trade. Mou et al [35] have revealed the relevance and cargo flow mode of regional maritime trade patterns along the MSR through different types of maritime networks.…”
mentioning
confidence: 99%